The role of diffusion-weighted MRI in the evaluation of imaging for prostate carcinoma: A systematic review - Komal Mishra; Asish Pavanan; Pratapsingh Hanumansingh Parihar (MGM Journal of Medical Sciences)
Background: Prostate cancer is one of the most common cancers in men. In recent times, diffusion-weighted imaging (DWI) sequence magnetic resonance imaging (MRI) techniques have been used in the diagnosis of prostate cancer. The present systematic review aims to analyze the effectiveness of DWI in diagnosing prostate cancer. Methodology and Results: Publicly available English databases, such as PubMed and Google Scholar, were searched until 2020. We reviewed 965 research articles, and 10 were selected based on inclusion and exclusion criteria. The study found that the apparent diffusion coefficient (ADC) value decreases as the total diffusion volume increases. Tumor cells have significantly lower ADC values compared to normal or non-tumor cells. DWI was found to have higher sensitivity and accuracy than the T2W MRI technique. However, Choline-PET/CT was slightly more effective in diagnosing prostate cancer compared to DWI. Conclusion: DWI is a promising MRI technique that can enhance diagnostic performance in conjunction with other conventional MRI techniques to diagnose prostate cancer.